2020
DOI: 10.1159/000505519
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Outcomes in Hypoxic-Ischemic Encephalopathy following Hypothermia: A Meta-Analysis

Abstract: <b><i>Introduction:</i></b> Prediction of neurodevelopmental outcome in infants with hypoxic-ischemic encephalopathy remains an important challenge. Various studies have shown that the predictive ability of different modalities changed after the introduction of therapeutic hypothermia. This paper reviews the diagnostic test accuracy of the different modalities that are being used to predict neurodevelopmental outcomes following therapeutic hypothermia. <b><i>Methods:</i&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 80 publications
(218 reference statements)
3
69
1
Order By: Relevance
“…Damage to the parasagittal cortex in term infants after HI is highly associated with poor neurodevelopmental outcomes including cognitive and learning deficits and epilepsy [28][29][30][31]. In the present study, cerebral ischemia in near-term fetal sheep was associated with a pattern of parasagittal cortical damage after 7 days of recovery, which included a marked reduction in the survival of cortical GAD + , parvalbumin + , calretinin + , and calbindin + interneuron populations.…”
Section: Discussionsupporting
confidence: 45%
“…Damage to the parasagittal cortex in term infants after HI is highly associated with poor neurodevelopmental outcomes including cognitive and learning deficits and epilepsy [28][29][30][31]. In the present study, cerebral ischemia in near-term fetal sheep was associated with a pattern of parasagittal cortical damage after 7 days of recovery, which included a marked reduction in the survival of cortical GAD + , parvalbumin + , calretinin + , and calbindin + interneuron populations.…”
Section: Discussionsupporting
confidence: 45%
“…These tools are certainly useful but generally, they are used on specific indication. For instance, continuous and amplitude-integrated EEG and somatosensory evoked potentials are applied in infants with hypoxic-ischemic encephalopathy (HIE) [ 41 , 42 ] and sensory assessments are used in preterm infants with behavioral issues [ 43 , 44 ]. Therefore, these instruments fall beyond the scope of this review.…”
Section: Early Detection Of Developmental Disordersmentioning
confidence: 99%
“…4) A brain magnetic resonance imaging (MRI) scan is conducted to determine the extent and degree of brain injury in infants with HIE. 3,4) Many additional tests, such as diffusion-weighted imaging (DWI), diffusion-tensor imaging, and proton magnetic resonance spectroscopy ( 1 H-MRS), have recently been used. [3][4][5] Ouwehand et al 4) performed a meta-analysis of the predictors of outcomes in HIE following hypothermia using 37 articles on aEEG, MRI, DWI, and 1 H-MRS.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…3,4) Many additional tests, such as diffusion-weighted imaging (DWI), diffusion-tensor imaging, and proton magnetic resonance spectroscopy ( 1 H-MRS), have recently been used. [3][4][5] Ouwehand et al 4) performed a meta-analysis of the predictors of outcomes in HIE following hypothermia using 37 articles on aEEG, MRI, DWI, and 1 H-MRS. This study showed that abnormal aEEG findings at 36 h (diagnostic odds ratio [DOR], 62.7; 95% CI, 19.5-202.0; P < 0.001), injury to the posterior limb of the internal capsule on MRI (DOR, 39.5; 95% CI, 16.9-92.3; P < 0.001) or the thalami on DWI (DOR, 50.2; 95% CI, 19.1-131.7; P < 0.001), and an increased lactate/N-acetylaspartate peak on 1 H-MRS within 7 days (DOR, 64.8; 95% CI, 28.8-145.9; P < 0.001) are strong predictors of adverse neurodevelopmental outcomes.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation